Utilizing Cigarette Filter Waste Extract as a Natural Pesticide to Eradicate Whitefly Pests in Chili Plants (Capsicum frutescens L.) - Fiqri Algamar; Khairul Rizal; Novilda Elizabeth Mustamu; Siti Hartati Yusida Saragih (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Chili pepper (Capsicum frutescens L.) is a plant commonly cultivated in Indonesia. This research employed an empirical, quantitative experimental approach using a Randomized Block Design (RBD). The study included three treatment groups with varying concentrations of cigarette butt biopesticides: a control group, and treatment groups at 10 ml/L, 20 ml/L, and 30 ml/L. The results indicated that biopesticides derived from cigarette butt waste extracts significantly affected the control of whitefly pests on chili peppers. The ANOVA test yielded an F value of 150.044 with a significance level of 0.000, demonstrating a highly significant difference among the treatments. The control group exhibited the highest average mortality rate of 62.22% for pests, followed by the 10 ml/L treatment at 50.67%, the 20 ml/L treatment at 42.67%, and the 30 ml/L treatment, which was the least effective, with an average mortality rate of 32.00%. These findings suggest that higher concentrations of the extract are more effective in reducing the number of living pests, positioning this biopesticide as an environmentally friendly alternative for pest control.